The epidemic of stroke mortality attributed to high body mass index in mainland China: Current trends and future prediction - Du, Zhaoqing; Zhu, Wenxuan; Zhao, Yuqi; Liu, Shenghang; Chu, Hao; Sun, Zhonghe; Chu, Meng (Frontiers in Public Health, 2022)
Background High body mass index (BMI) is an important risk factor for stroke. The aim of this study was to assess the long-term trend of high BMI-attributed stroke mortality and make projections through 2030. Methods Data were extracted from the Global Burden of Disease Study 2019 and World Population Prospects 2019. An age-period-cohort framework was used in the analysis. Results From 1990 to 2019, the age-standardized mortality rate (ASMR) of high BMI-attributed stroke among females decreased by 15.2%, while among males, it increased by 31.1%. All of the age groups studied showed an increasing pattern over the last 30 years in males, and in women, the age groups encompassing participants who were 25-69 years old showed a decreasing pattern. In the same birth cohort, high BMI-attributable stroke mortality rates increased exponentially with age in both sexes. For females, the period rate ratios (RR) showed a downward trend after 2000-2004, and the cohort RR also showed a downward trend after the birth cohort 1928-1932. For males, the RR showed an upward trend, but this increase was halted in the most recent period, and the cohort RRs showed a monotonic increasing pattern. It was projected that the ASMR of high BMI-attributed stroke would decrease among females and increase among males in the near future and that the proportion of elderly individuals with death due to high BMI-attributed stroke was projected to increase. Conclusions Over the last three decades, the high BMI-attributed stroke mortality rate decreased among females and increased among males, and these trends are projected to continue in the future. In addition, the proportion of elderly individuals with high BMI-attributed stroke mortality was projected to increase gradually in both men and women. More health-promoting efforts are needed, especially for elderly individuals and males.